ANALISIS PENGARUH FINANCIAL STABILITY, PERSONAL FINANCIAL NEED, EXTERNAL PRESSURE, DAN INEFFECTIVE MONITORING PADA FINANCIAL STATEMENT FRAUD DALAM PERSPEKTIF FRAUD - Nur Maghfiroh; Komala Ardiyani; Syafnita Syafnita (Jurnal Ekonomi Dan Bisnis, 2016)
This research aims to identify and analyze the effectiveness of the fraud triangle in detecting financialstatement fraud. The variables of the fraud triangle are used a  proxy financial stability withACHANGE, personal financial need that proxy  by OSHIP,  external pressure that proxy by FREEC andineffective monitoring by BDOUT proxy. Detecting of financial statement fraud in this  research uses aproxy earnings management.  The population of this research is the manufacturi ng companies listed on Indonesia Stock Exch angein 2011 and 2012. Total samples of this research are 34 manufacturing companies. Statisti cal d ataanalysis method used is linear regression. The result of this research indicate that the extern al pressure (FREEC) influence the financialstatement fraud. Meanwhil e, the financial stability pressure (ACHANGE), personal financial need(OSHIP ) and ineff ective monitoring (BDOUT ) has  no significant impact on financial statement fraud.  Keywords  : financial statement fraud, financial stability, personal financial